Analisis Positioning Nike - Noyanta Luga; Rachel Mia L. Lumbantoruan; Evi Enitari Napitupulu; Rizki Indah Fitria; Sharly Sianturi (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Nike produces a wide range of sports equipment such  as running shoes, sportswear, football, basketball, tennis, golf, etc. Now Nike follows global fashion trends and is well known and popular in youth culture and hip hop culture to supply several fashion products. In this research, an analysis of Nike's positioning was carried out starting from distribution, value, product plans, development and promotion, advertising division to investigating Nike's superiority in the global market and comparing it with competitors. Nike's strategy focuses on consumers who love Nike and drives product value to higher levels. Customers who perceive a product to be of high quality are likely to pay high prices more often and consistently. Once consumers develop product intimacy, they will associate themselves with the product and will pay whatever price is listed on the product. The results of research using analysis explain that Nike remains and continues to be at the forefront in creating and distributing clothing and types of sports equipment. However, Nike should consider focused loads too heavy and not allow "rest on top". Negative impacts of Nike's central promotion system, for example, advertising that is too high, raw material costs affected by global finance, representation practices that have a negative impact on Nike's brand image. Likewise the dangers of Nike's central advertising system, for example Nike cannot keep up with world design trends, its benefits are affected by money trade and financial downturns as it expands throughout the world.